2018
DOI: 10.9758/cpn.2018.16.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype Analysis of Paraoxonase 1 in Schizophrenic Patients Treated with Atypical Antipsychotics

Abstract: ObjectiveRecent studies suggest a possible involvement of low paraoxonase 1 (PON1) enzyme activities in the association between schizophrenia, treatment with atypical antipsychotics and increased cardiovascular (CVD) risk. In the present study, we aimed at investigating the PON1 status in a group of schizophrenic patients treated with either olanzapine or other antipsychotic, as compared to a group of healthy control participants.MethodsWe assessed the arylesterase (AREase) and paraoxonase (POase) activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In polymedicated SCZ patients, most studies report normal AREase [12,53] and POase [53][54][55][56] activities. Lower AR-Ease activity was reported by Paval et al [57], who also reported lowered POase activity in QQ patients taking olanzapine, but not other atypical antipsychotics. Ünsal et al [58] found lower POase activity in patients who were taking olanzapine (data not adjusted for PON1 Q192R genotype), but not quetiapine.…”
Section: Pon1 and Schizophreniasupporting
confidence: 47%
See 1 more Smart Citation
“…In polymedicated SCZ patients, most studies report normal AREase [12,53] and POase [53][54][55][56] activities. Lower AR-Ease activity was reported by Paval et al [57], who also reported lowered POase activity in QQ patients taking olanzapine, but not other atypical antipsychotics. Ünsal et al [58] found lower POase activity in patients who were taking olanzapine (data not adjusted for PON1 Q192R genotype), but not quetiapine.…”
Section: Pon1 and Schizophreniasupporting
confidence: 47%
“…Regarding PON1 polymorphisms, neither Matsumoto et al [62] or Paval et al [57] found an association between the Q192R polymorphism and SCZ. On the other hand, Kuçukali et al [59] reported that the RR genotype was more prevalent in SCZ patients than controls, whilst Paval et al [57] reported that the LL genotype was more prevalent in SCZ.…”
Section: Pon1 and Schizophreniamentioning
confidence: 90%
“…In patients with chronic schizophrenia, on the other hand, there was no significant decrease in PON1 activity (Boll et al, 2017), although the lack of any changes in PON1 activity could be explained by stimulatory effects of risperidone on PON1 activity . A recent study suggests a possible involvement of low CMPAase in the increased cardiovascular (CVD) risk in patients with SCZ (Pavăl et al, 2018). Gupta et al (2011) found lower CMPAase PON1 activity in CVD patients as compared to controls, independent of age, sex, smoking, alcohol and HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence that resolves the question of whether genetic variants in MTHFR C677T impair the efficacy of MTHFR in converting 5,10-MTHF to 5-MTHF formation in schizophrenia patients. The PON1 SNP variant was reported to provide a protective role; however, the genotypes, 192 QR and RR, are associated with higher levels of homocysteine [11], and significantly lower AREase activity was found in schizophrenic patients, along with significantly lower PONase activity in olanzapine-treated patients with the QQ genotype [12].…”
Section: Introductionmentioning
confidence: 99%